New Business Models And Editorial Exemption: A Study On Service Journalism Based On Ecommerce Operations // Novos Modelos De Negócios E Isenção Editorial: Um Estudo Sobre O Jornalismo De Serviço Com Base Em Operações De Comércio Eletrônico - Belda, Francisco Rolfsen (Contemporanea, 2014)
The paper presents and discusses business strategies based on the association from journalistic content to new commercial practices in digital media. We describe selected examples from Folha de S. Paulo and El País involving service guides, links and ecommerce advertisements. The employed method provides content analysis to illustrate how the search for new business models in journalism may conduct its commercial activities beyond the conventional sale of advertising and subscriptions, including a discussion on the challenges and implications of this practice. The hypothesis is demonstrated by describing operations for the sale of tickets, books, music, and films related to news features and service journalism contents. The text finally wonders and discusses how such commercial actions may affect editorial autonomy and publishing exemption.